Small Molecules for Multi-Wavelength Near-Infrared Fluorescent Mapping of Regional and Sentinel Lymph Nodes in Colorectal Cancer Staging - Baart, Victor M.; Deken, Marion M.; Bordo, Mark W.; Bhairosingh, Shadhvi S.; Salvatori, Daniela C. F.; Hyun, Hoon; Henary, Maged; Choi, Hak Soo; Sier, Cornelis F. M.; Kuppen, Peter J. K.; van Scheltinga, Anton G. T. Terwisscha; March, Taryn L.; et al. (Frontiers in Oncology, 2020)
Assessing lymph node (LN) status during tumor resection is fundamental for the staging of colorectal cancer. Current guidelines require a minimum of 12 LNs to be harvested during resection and ultra-staging regional lymph nodes by sentinel lymph node (SLN) assessment is being extensively investigated. The current study presents novel near-infrared (NIR) fluorescent dyes for simultaneous pan lymph node (panLN; regional) and SLN mapping. PanLN-Forte was intravenously injected in mice and assessed for accumulation in regional LNs. SLN800 was injected intradermally in mice, after which the collection and retention of fluorescence in SLN were measured versus indocyanine green (ICG) and its precursor, SLN700, as references. LNs in the cervical, inguinal, jejunal, iliac, and thoracic basins could clearly be distinguished after a low dose intravenous injection of PanLN-Forte. Background fluorescence was significantly lower compared to the parent compound ZW800-3A (p < 0.001). SLN700 and SLN800 specifically targeted SLNs with fluorescence being retained over 40-fold longer than the current clinically used agent ICG. Using SLN700 and SLN800, absolute fluorescence in SLN was at least ten times higher than ICG in second-tier nodes, even at 1 hour post-injection. Histologically, the fluorescent signal localized in the LN medulla (PanLN-Forte) or sinus entry (SLN700/SLN800). PanLN-Forte and SLN800 appear to be optimal for real-time NIR fluorescence imaging of regional and SLNs, respectively.